Pengaruh Latihan Koordinasi Mata Kaki Dan Kelincahan Terhadap Kemampuan Dribbling SSB Putra Wijaya - Muhammad Razif; Romi Mardela; Afrizal s; Hendri Irawadi (Universitas Negeri Padang, 2020)
The problem in this research is that theability Dribbling of SSB Putra Wijaya Padang players is still not good. This research is to improve theability Dribbling through ankle coordination training and the agility of SSB Putra Wijaya Padang players. The purpose of this study was to determine the effect of ankle coordination training and agility on theability Dribbling at SSB Putra Wijaya Padang. This type of research is a quasi-experimental. This research was conducted in August - September 2020 at the Kompi A football field, Lapai, Padang City. The population in this study were all SSB Putra Wijaya Padang players totaling 83 people. The sample collection technique in this study was purposive sampling, so the sample in this study U-17 years amounted to 19 people. The instrument in this study was to use thetest Dribbling zigzag. The data analysis technique used in this study was the t test statistical analysis technique. Based on data analysis using t-test statistics, the results of this study indicate the effect of ankle coordination training and agility on theability dribbling of SSB Putra Wijaya players (7,4> 1,734). Obtained an average value of the pre-test = 20.63 and the average value of the post-test = 19.89. This means that there is a significant effect of training oncoordination and agility on theability of dribbling anklePutra Wijaya Ssb players.